PENGARUH AROMATERAPI LAVENDER TERHADAP PERUBAHAN TINGKAT NYERI IBU PASCA SEKSIO SESAREA - jupri yono (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2016)
Abstrac: This research has purpose to find the Lavender aromatherapy effect on changing the post sectio caesarean pain level. Research design will use Pra-Eksperimantal with On-Group Pra-Post Test Design. The population are all of post sectio caesarean patient from 29 june to 29 July 2016 with total 21 respondents. Total sampels are 18 that chosen base on inclusion criteria by using Purposive Sampling. Variable Measurements used Numeric Rating Scale. Data Analyzing used Wilcoxon Signed Rank Test on Computer Program with α = 0.05, the result showed Pvalue = 0,002. Because P < α So it can be concluded that Lavender Aromatherapy give significant effect to changing the post sectio caesarean pain level.